Chess In Medical Education At Umanand Prasad School Of Medicine & Health Sciences (Upsm&Hs) In Fiji - Ricardo Gregorio C. III; Oremo, Judith; Narayan, Aayush; Chand, Pavitra; Chand, Aniketh; Chand, Nikil (Մանկավարժ հրատ․)
Chess is a board game played by two people against each other. Chess is an abstract strategy game with no hidden information. It is played on a chessboard with a 64-square square grid and a 64-square square chessboard. At the start, each player has sixteen pieces (one king, one queen, two rooks, two knights, two bishops, and eight pawns): one king, one queen, two rooks, two knights, two bishops, and eight pawns. To acquire relevant information for the study, a literature review and a survey were done. The study's goal was to identify the link between chess and cognitive development in medical students, as well as the relationship between various game kinds and the multiple advantages the students received, and to correlate the level of chess players with their academic achievement. This study found that chess has an influence on or increases abilities in learning and development. Playing chess produces the phenomenon of repeating, practicing, and mastering a strategy to influence the game result; similarly, on a learning platform, this method aids in memory retention of knowledge. Repetition, practice, and mastery are important in medical education because medical internships and residencies build students' confidence, knowledge, and practical skills. Correspondence rounds are preferred at the starting level to assist learning of chess lessons, and as one improves, they progress to Rapid, Blitz, and Bullet. More study is needed before educators may be deployed or taught to utilize chess in the classroom. A well monitored research survey may also provide a more definitive evaluation of the impact of chess in medical education in universities.
Keywords: Chess